ANALISIS TINGKAT KERENTANAN WILAYAH GEMPABUMI JALUR SESAR SIANOK KOTA BUKITTINGGI - ghinna rahmatania; Helfia Edial (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
This research was conducted in the city of Bukittinggi, which aims to find out: 1) Prone to earthquake hazards, 2) regional vulnerability to earthquakes. The method used in this research is descriptive quantitative approach and the data used was secondary data. The results of this study indicate that earthquake hazard prone areas are influenced by physical factors such as peak ground acceleration (PGA), geological structure, geological formation, and slope. The earthquake hazard prone classification is in two classes, that is low hazard prone classes scattered in the eastern part of Bukittinggi City, and medium hazard prone that spread in the north to the weastern part of Bukittinggi City. Regional vulnerability to earthquake is influenced by physical conditions in the form of earthquake hazard prone and earthquake vulnerability index. Regional vulnerability to earthquakes is divided into three classifications, that is low regional vulnerability spread in the southern part of Bukittinggi City, medium regional vulnerability is being spread in the east to south part of Bukittinggi City, and high regional vulnerability is spread in the west to middle part of Bukittinggi City.